2016
DOI: 10.1016/j.bbadis.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus protein A enhances osteoclastogenesis via TNFR1 and EGFR signaling

Abstract: Staphylococcus aureus is a major causative agent of osteomyelitis in adults and children. The increasing incidence of antimicrobial resistant isolates and the morbidity of this type of infection denote that alternative therapeutic approaches are required. S. aureus protein A interacts with TNFR1 and EGFR expressed at the surface of host cells. Given the importance of TNF-α and EGFR/RANKL crosstalk in enhancing osteoclast differentiation, the aim of this study was to determine the role of protein A in the induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 47 publications
0
33
0
1
Order By: Relevance
“…In addition to the typical inflammation symptoms, the most characteristic of these diseases is accompanied by excessive bone destruction and bone non-union (Olson & Horswill, 2013). Previous reports demonstrated that the femoral bone mass was lost about 10-20% in rat models which were infected by S. aureus (Mendoza Bertelli et al, 2016). In case of trauma or surgery, S. aureus could break through the host barrier for local colonization, is extremely easy to produce bacterial biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the typical inflammation symptoms, the most characteristic of these diseases is accompanied by excessive bone destruction and bone non-union (Olson & Horswill, 2013). Previous reports demonstrated that the femoral bone mass was lost about 10-20% in rat models which were infected by S. aureus (Mendoza Bertelli et al, 2016). In case of trauma or surgery, S. aureus could break through the host barrier for local colonization, is extremely easy to produce bacterial biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the over activation of epidermal growth factor receptor (EGFR) signalling in S. aureus ‐infected bone (Chen, Yao, et al, 2018; Mendoza Bertelli et al, 2016). Epidermal growth factor receptor (EGFR) is a key molecule regulating cell survival (Liu et al, 2019; Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the primary function of SpA is immune evasion, studies have documented its direct role in bone infection. It was shown that SpA can directly bind to osteoblasts, mediating cell death, inhibition of bone formation (osteogenesis), and induction of bone resorption (osteoclastogenesis) (51)(52)(53)(54). The importance of osteoclastic activity in osteomyelitis is becoming evident, and therefore many studies have emerged to examine the effects of S. aureus in promoting osteoclastogenesis and osteoclastic activity.…”
Section: Staphylococcal Colonization Of Bonementioning
confidence: 99%